2020
DOI: 10.1007/s10107-020-01574-2
|View full text |Cite
|
Sign up to set email alerts
|

Optimal sampled-data controls with running inequality state constraints: Pontryagin maximum principle and bouncing trajectory phenomenon

Abstract: Sampled-data control systems have steadily been gaining interest for their applications in Engineering and Automation. In the present paper we derive a Pontryagin maximum principle for general nonlinear optimal sampled-data control problems in the presence of running inequality state constraints. In particular we obtain a nonpositive averaged Hamiltonian gradient condition associated to an adjoint vector being a function of bounded variations. As a well-known challenge, theoretical and numerical difficulties m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…Finally a maximal velocity minimization problem for the harmonic oscillator with sampled-data control is numerically solved in Section 4.2 using a shooting method based on the necessary conditions provided in Theorem 3.7. As in the recent work [18], a bouncing trajectory phenomenon is observed (see Figs. 1 and 2).…”
Section: Contributions Of the Present Papersupporting
confidence: 83%
See 4 more Smart Citations
“…Finally a maximal velocity minimization problem for the harmonic oscillator with sampled-data control is numerically solved in Section 4.2 using a shooting method based on the necessary conditions provided in Theorem 3.7. As in the recent work [18], a bouncing trajectory phenomenon is observed (see Figs. 1 and 2).…”
Section: Contributions Of the Present Papersupporting
confidence: 83%
“…2.6). More recently Bourdin and Dhar have extended in [18] the previous work to the state constrained case. In that context the authors have observed and studied a particular behavior of the trajectories with respect to the state constraints, called bouncing trajectory phenomenon.…”
Section: Continuous-time Optimal Sampled-data Control Problemsmentioning
confidence: 99%
See 3 more Smart Citations